University Smart Guidance Counselling; Smart Innovation, Systems and Technologies; Vol. 59 : Smart Education and Smart e-Learning - Belskaya E. Ya. Elena Yakubovna; Moldovanova E. A. Evgeniya Aleksandrovna; Rozhkova S. V. Svetlana Vladimirovna; Tsvetkova O. Olga; Chervach M. Yu. Mariya Yurievna (2016, 2016)
Title screen